Regional restructuring in a transition economy: the process of tertiarization in Slovakia - Milan Bucek; Rudolf Pastor (European Regional Science Association (ERSA), 2002)
Slovakia is influenced by the process, that is connected with global ones in economy. During the pre-transformation period, the socialist system did not develop the tertiary sphere. The transformation process brought after the year 1989 a remarkable change in economic structure. One of the crucial problems is high rate of unemployment namely in the regions that collapsed in many branches of production. Despite dynamic economic changes, the rate of unemployment did not raise so high, as the increasing development of tertiary sphere swallowed the striking flow of unemployment in the primary and secondary sectors. Looking at the needs and the trends of development of the tertiary sphere, we cannot forget its international dimension. The most remarkable internationalization will be seen in modern information activities, foreign trade, financial services, FDI etc. Analyses carried out, emphasizing the new type of reproduction process in the matter, have proved the fact, that the further development of the country should be more connected with our human investments. The concepts of "information age", "information society" and "knowledge based-economy" basically contain arguments to the effect that, in the advanced economies, knowledge and information are becoming the principal factors of production. There is a visible parallel with investments in education, development of science, etc. If we want to enforce a higher effectiveness of production, it is only possible through the development of a broad spectrum of tertiary activities. Our paper try to analyze this changes on the basis of available statistical data. Transition process is closely connected with restructuring process. From managing of this process depends if Slovakia will capture the global wave of changes from industrial to advanced services, but not only on country level but also in their regional dimension.
Keywords: 330